Intercellular communication between macrophages, myoblasts and fibroblasts in the context of rheumatoid arthritis-associated skeletal muscle wasting - Ollewagen, Tracey (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.